Photochemical dissociation of water, reduction of inorganic carbon and fixation of nitrogen by apatite - Bahadur, Krishna; Ranganayaki, S.; Verma, P.; Kumar, S. (1981)
Apatite has been found to dissociate water and showed photochemical liberation of proton, which can be used in the photochemical reduction of inorganic carbon to organic carbon and fixation of free molecular nitrogen to nitrogenous compounds.